Biochemical and molecular characterization of novel keratinolytic protease from Bacillus licheniformis (KRLr1) - Rahimnahal, Somayyeh; Meimandipour, Amir; Fayazi, Jamal; Asghar Karkhane, Ali; Shamsara, Mehdi; Beigi Nassiri, Mohammadtaghi; Mirzaei, Hamed; Hamblin, Michael R.; Tarrahimofrad, Hossein; Bakherad, Hamid; Zamani, Javad; Mohammadi, Yahya (Frontiers in Microbiology, 2023)
The keratin-degrading bacterium Bacillus licheniformis secretes a keratinase with potential industrial interest. Here, the Keratinase gene was intracellularly expressed in Escherichia coli BL21(DE3) using pET-21b (+) vector. Phylogenetic tree analysis showed that KRLr1 is closely related to Bacillus licheniformis keratinase that belongs to the serine peptidase/subtilisin-like S8 family..Recombinant keratinase appeared on the SDS-PAGE gel with a band of about 38 kDa and was confirmed by western blotting. Expressed KRLr1 was purified by Ni-NTA affinity chromatography with a yield of 85.96% and then refolded. It was found that this enzyme has optimum activity at pH 6 and 37 °C. PMSF inhibited the KRLr1 activity and Ca2+ and Mg2+ increased the KRLr1 activity. Using keratin 1% as the substrate, the thermodynamic values were determined as Km 14.54 mM, kcat 912.7 × ¬10–3 (S−1), and kcat/Km 62.77 (M−1 ¬S−1). Feather digestion by recombinant enzyme using HPLC method, showed that the amino acids cysteine, phenylalanine, tyrosine and lysine had the highest amount compared to other amino acids obtained from digestion. Molecular dynamics (MD) simulation of HADDOCK docking results exhibited that KRLr1 enzyme was able to interact strongly with chicken feather keratine 4 (FK4) compared to chicken feather keratine 12 (FK12). These properties make keratinase KRLr1 a potential candidate for various biotechnological applications.